KONSEKUENSI YURIDIS PERJANJIAN BERBAHASA ASING DAN DAMPAKNYA BAGI PERKEMBANGAN MASYARAKAT EKONOMI ASEAN - Laheri, Putu Eva (Jurnal Advokasi, 2017)
This writing is made in relation to discuss regarding the legal consequences for the agreement which made in foreign language pursuant to the legal consideration as stipulated in the supreme court decision no. 601 K/PDT/2015 and Supreme Court decision No. 595/K/ PDT-SUS/2010 which we conclude the ability and accuracy of the judges hold a very important role in deciding and giving legal considerations relating to the application of cancellation of the agreement which made in foreign language in order to make a decision and judgment which are able to give a sense of justice, legal certainty and expediency which provides security to invest in Indonesia in this era of the ASEAN Economic Community (AEC).